The Translation Techniques on Rupi Kaur’s The Sun and Her Flowers Based on the Lefevere's Perspective - K. Harnadi, Kunkun; Lufiani, Riska; Supian; Maulana, Angga (JOMANTARA, 2024)
This topic was chosen to analyze the translation techniques in translating the poem-poetry anthology entitled The Sun and Her Flowers wrote by Rupi Kaur, translated into Indonesian by Ni Made Purnamasari. In analyzing the poem, the writer employs the theory of Lefevere's (1975), which includes seven techniques, they are 1) phonemic translation, 2) literal translation, 3) metrical translation, 4) poetry into prose translation, 5) rhymed translation, 6) blank verse translation, and 7) interpretation. The method is used in this research is descriptive qualitative, applies documentationstrategies. The writer collects data through multiple phases: collection, analysis, and identification. The Lefevere's perspectives are employed to figure out the techniques of translation to translate the anthology. 20 poems were chosen for this research as the sample. The resultsrevealed that 18 poems applied literal translation, 1 applied metrical translation, 2 applied rhymed translation, 3 applied blank verse translation, and 5 applied interpretation translation. The number of translation techniques used in each poem is as follows: 1 poem uses 3 translation techniques, 7 poems use 2 translation techniques, and 12 poems use only one translation technique.